2009
DOI: 10.1002/pmj.20143
|View full text |Cite
|
Sign up to set email alerts
|

Information Systems Project Management in PMJ: A Brief History

Abstract: The Project Management Institute (PMI) plays an important role in the training, career development, and recognition of information systems (IS) project managers. Indeed, not only do IS professionals account for a large proportion of the PMI constituency, but PMI is also influential in the training of IS project managers. This study explores further the contribution of PMI to IS project management by means of its main publication outlet, the Project Management Journal (PMJ). To do so, the contents of the 39 IS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Henderson (2008) reported that “project manager competencies in decoding and encoding communication significantly contribute to team member satisfaction and productivity” (p. 48). The importance of project manager communication was given further attention in the literature, when Zhang (2011) posited the necessity of two‐way communication for the effective management of project risks; Yasin, Gomes, and Miller (2009) noted the importance of leadership and communication; and Rivard and Dupré (2009) found a relationship between strong communication processes and healthy stakeholder management. Considering the significant and historical empirical evidence supporting the importance of project manager communication, we believe potential obstacles to communication should be investigated and discussed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Henderson (2008) reported that “project manager competencies in decoding and encoding communication significantly contribute to team member satisfaction and productivity” (p. 48). The importance of project manager communication was given further attention in the literature, when Zhang (2011) posited the necessity of two‐way communication for the effective management of project risks; Yasin, Gomes, and Miller (2009) noted the importance of leadership and communication; and Rivard and Dupré (2009) found a relationship between strong communication processes and healthy stakeholder management. Considering the significant and historical empirical evidence supporting the importance of project manager communication, we believe potential obstacles to communication should be investigated and discussed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The project management for organizational IT capability is associated with the ability to manage the IT project within an organization or across many organizations effectively [39,40]. It includes technical tools, an organizational structure for guiding and evaluating project performance, a more comprehensive perspective on governance and policy goals.…”
Section: Hypotheses 3 (H3) Financial Resources Have a Significant Inmentioning
confidence: 99%
“…Despite efforts made by researchers and professional organizations like the Project Management Institute (PMI) and International Project Management Association, some projects still fail. This causes major concern to professionals and organizations in understanding the factors that lead to project success and failure [2][3][4][5]. The authors in [6] conducted a longitudinal study involving 51 database development teams.…”
Section: Introductionmentioning
confidence: 99%